Arts for Business: Creative Co‑operation for Innovation and Sustainable Development of the Company as a Brand and Community - Szczepaniak , Katarzyna (Edukacja Ekonomistów i Menedżerów, 2018)
In Poland, the value of art as a contributor and equal collaborator for business is still either not fully recognized or undervalued. Thus, the aim of the article is to present a set of effective practices and research, highlighting examples from Poland and focusing on areas of creative collaboration beneficial for entrepreneurs, such as employees’ development and empowerment, artistic residences, and investing in artists seen as brands or simply hiring them as chief innovators and inspirers, not only instructors. Finally, the benefits in the field of human capital and communication are briefly discussed to encourage Polish business practitioners to strengthen and extend the art‑business collaboration for the sake of the sustained socio‑economic development.